Contestation of Global Competencies: The Concepts of 3 Featured Madrasah Ibtidaiyah in Banyumas - Rahman Afandi; Mustajab Mustajab (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
The existence of madrasah (Islamic school) management development is essential in Indonesia. Research findings in 2017 show the pattern of educational expansion carried out by madrasahs in each region and education unit. Madrasahs inflate their roles and functions as a means of quality improvement. The expansion can be seen in the progressing number of Madrasah Ibtidaiyah (MI) in Banyumas, reaching a figure of 182. The group MI divided into 179 private institutions and three public ones. The madrasah spread in 27 sub-districts of Banyumas District. Problems faced by MTs in Banyumas in developing their potentials are related to global competencies. The issues have become the homework for madrasah managers who oversee quality excellence. This paper will discuss three featured MIs in Banyumas in relation with the contestation of global competencies in Islamic education management. The three madrasahs are the State Madrasah Ibtidaiyah number 1 Banyumas (MI Negeri 1 Banyumas) as a Distinguished and Islamic School; MI Ma'arif NU Pageraji as a School of Champions; and MI Muhammadiyah Karanglewas Kidul as a School of Quality and Character. Keywords: Global Competence, Superior Madrasah Concept Abstrak Keberadaan perkembangan manajemen madrasah penting di Indonesia. Hasil riset tahun 2017, pola eloborasi pendidikan dilakukan madrasah di masing-masing daerah dan satuan pendidikan. Madrasah mengembangkan peranan dan fungsi sebagai pola peningkatan mutu. Hal ini terlihat pada progresifitas Madrasah Ibtidaiyah (MI) Banyumas. Hal ini terlihat dari jumlah 182 MI. Madrasah terbagi dalam 179 MI swasta dan 3 MI Negeri. Madrasah tersebuttersebar di 27 kecamatan Kabupaten Banyumas. Problematika MI banyumas dalam mengembangkan potensi diri berdasar pada kompetensi global. Hal tersebut menjadi PR para pengelola madrasah dalam keunggulan mutu. Paper ini akan membahas 3 MI unggulan Banyumas dalam kontestasi kompetensi manajemen Pendidikan islam global. Hal tersebut dapat dicirikan oleh MI Negeri 1 Banyumas sebagai Sekolah Unggul dan Islami, MI Ma'arif NU Pageraji. sebagai Sekolah Para Juara, dan MI Muhammadiyah Karanglewas Kidul sebagai Sekolah Bermutu dan Berkarakter. Kata Kunci: Kompetensi Global, Konsep Madrasah Unggulan